Effects of skipped spawning on the reproductive potential of argentine hake (Merluccius hubbsi) - Macchi, Gustavo Javier (2017)
We analyzed the effect of skipped spawning on the estimates of length and age at maturity and on the reproductive potential of Argentine hake (Merluccius hubbsi) from the Patagonian stock during the spawning peaks between 2005 and 2013. The length at first maturity increased by 2–3 cm in total length (TL), and the age at maturity increased by 0.27–0.88 years when the proportion of females that would skip spawning was incorporated in the relationships. In addition, the slopes of the models decreased, suggesting that all individuals reach sexual maturity at a greater size and age than those estimated with the traditional criterion for maturity, which does not consider skipped spawning because fish in the resting stage are classified as mature. The reduction in egg production caused by skipped spawning ranged between 3.56% and 12.12%, when we used the maturity models with age data, or between 2.70% and 6.80%, when we used the models with TL data. Females that would skip spawning were mainly specimens with sizes between 40 and 50 cm TL, and most belonged to the age class of 3-year-old fish.